Education for sustainability in tourism. A handbook of processes, resources, and strategies. - (:unkn) unknown (Springer, 2015)
Sustainability is a dominant theme in tourism practice. Increasingly, research and education of tourism stakeholders is also necessary in improving sustainable tourism practice. This book pays systematic attention to education for sustainability in tourism, and is thus a valuable resource for sustainable tourism educators and scholars. The book is divided into four parts. Part I provides a reference for educators seeking to understand core knowledge areas, ethics, corporate social responsibility and governance. Part II examines issues and processes relevant to understanding tourism and sustainability in the formal educational sector, including universities, vocational training and school settings. Part III explores learning and sustainable tourism in non-institutional settings, including destination communities, coaching and mentoring and visitor learning. The final part provides a collection of cases to illustrate the use of different pedagogies and assessment approaches in education for sustainability in tourism. The book will be accompanied by instructor resources to assist educators teaching in the field.
Keywords: Fremdenverkehr; Umweltbewusstsein; Berufsausbildung; Weiterbildung; Nachhaltigkeit; Tourismus; Umwelterziehung; Ethik; Governance